THE ROLE OF PERCEIVED RISK ON ELECTRONIC WORD OF MOUNTH IN NORTH SUMATERA - Renny lubis; Syaifuddin Syaifuddin; Yusuf Ronny Edward (Journal of Management and Innovation Entrepreneurship (JMIE), 2026)
Incorrect marketing techniques can result in a decrease in consumer purchasing decisions. Marketing plays a crucial role in the business world. Therefore, it is crucial to examine the influence of risk perception on electronic word-of-mouth (EWOM) in North Sumatra. The risk perception variable serves as the independent variable, while electronic word-of-mouth serves as the intervening variable. This study employed a quantitative method, supported by extensive literature. All data from the variables were analyzed using structural equation modeling with a partial least squares approach, using SmartPLS software. The population consisted of online transaction users in North Sumatra. The sample size was 62 respondents. The analysis concluded that the influence of risk perception on electronic word-of-mouth (EWOM) in North Sumatra is positive and significant. Therefore, risk perception is crucial in enhancing all forms of communication, reviews, or testimonials about a product or service shared by consumers via the internet in North Sumatra.